Optimization of The Executorial Power of Peace Deeds Over Land Disputes and Conflicts Mediated by BPN - Said, Said; Wachdin, Syarif Zakaria Said; Adytia, Nur Amalina Putri (Fakultas Hukum Universitas Hang Tuah, 2024)
The aim of this research is to describe and analyze the settlement related to the peace deed that was agreed upon and signed by the parties in mediation by BPN. This research was carried out using literature study, collect secondary data, the approach used was a conceptual approach. It is hoped that the results of mediation will satisfy the parties and can be carried out well by the parties to the dispute. In this research, it was formulated to find out whether the agreed peace agreement had binding legal force even though it was not registered with the court and whether it still had executorial force. It is known in order to achieve benefits, justice and legal certainty. The legal consequences if the parties or one of the parties do not want to carry out the mediation peace deed, the trial can be continued. If the party breaks and does not implement the contents of the Deed of Agreement, then the party who feels aggrieved must file a lawsuit for breach of promise/default first against the party who does not implement the contents of the existing Deed of Agreement, so they must start the proceedings from the initial level first.